Transformasi Digital Dalam Laporan Keuangan Pemerintah: Peluang Dan Tantangan Di Pemerintah Daerah Kota Surakarta - ELIN DWI SAPUTRI; Angger Restu Bidari (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study analyzes the digital transformation of financial reporting in the Surakarta City Government within the context of the Fourth Industrial Revolution. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The results show that the adoption of technologies such as SAKTI and e-Budgeting has improved efficiency and transparency, but challenges remain, including limited human resources and system integration. This research contributes to understanding the implementation of digitalization at the local government level.